2019
DOI: 10.1029/2019jg005477
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variations in N2O Emissions in a Subtropical Forest With Exogenous Nitrogen Enrichment are Predominately Influenced by the Abundances of Soil Nitrifiers and Denitrifiers

Abstract: Elevated nitrogen (N) deposition has induced substantial impacts on the emissions of nitrous oxide (N 2 O) from forest ecosystems, but how soil microbes regulate the production/consumption of N 2 O under elevated N deposition remains poorly understood, particularly in high N deposition subtropical forests that are characterized by distinct wet-dry seasonality. We established a field N addition experiment in a subtropical forest in southern China to explore the influences of low, medium and high (35, 70, and 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 69 publications
(113 reference statements)
1
3
0
Order By: Relevance
“…The annual N 2 O emissions (0.39 ± 0.08–0.50 ± 0.02 kg N ha −1 yr −1 ) in the control plots of the current study are comparable to some previously reported values (0.39–0.52 kg N ha −1 yr −1 ) observed in some subtropical/tropical forests (Fan et al., 2017; Rowlings et al., 2012; Soper et al., 2018), but are much lower than those from other subtropical/tropical forests (0.70–3.50 kg N ha −1 yr −1 ; Han et al., 2019; Wieder et al., 2011; Xie et al., 2018; M. H. Zheng et al., 2016). Several potential mechanisms are responsible for the relatively low N 2 O emission in the current study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The annual N 2 O emissions (0.39 ± 0.08–0.50 ± 0.02 kg N ha −1 yr −1 ) in the control plots of the current study are comparable to some previously reported values (0.39–0.52 kg N ha −1 yr −1 ) observed in some subtropical/tropical forests (Fan et al., 2017; Rowlings et al., 2012; Soper et al., 2018), but are much lower than those from other subtropical/tropical forests (0.70–3.50 kg N ha −1 yr −1 ; Han et al., 2019; Wieder et al., 2011; Xie et al., 2018; M. H. Zheng et al., 2016). Several potential mechanisms are responsible for the relatively low N 2 O emission in the current study.…”
Section: Discussionsupporting
confidence: 91%
“…For instance, Han et al. (2019) found that experimental N addition (N addition hereafter) increased N 2 O emission under N poor conditions via stimulating the abundances of nitrifiers and denitrifiers, but decreased N 2 O emission in N rich conditions by depressing the abundances of denitrifiers in a subtropical forest. M. H. Zheng et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil pH can exert a direct and an indirect effect on biological properties (e.g., reductase activities, the abundance, and expression of functional genes, etc.) ( Liu et al, 2010 ; Hu et al, 2015 ; Han et al, 2019 ). The reductases for nitrate, nitrite, and nitric oxide are more active at pH <7 ( Gillam et al, 2008 ), while the N 2 O reductase activities are inhibited in soil with low pH ( Levy-Booth et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%